Determination of the effect of stress on the salivary cortisol level among sample of university students having myofacial pain - Rana M Hasan; Jamal N Ahmed (College of Dentistry/ University of Baghdad, 2014)
Background: Psychological stress is considered the major etiological factor precipitating myofacial pain and temporomandibular disorders.It is known that stress induce various adaptational responses of physiologic systems. The process includes increase in the activity of the hypothalamic-pituitary-adrenal axis which promotes cortisol secretion. Salivary cortisol has been used as a measure of free circulating cortisol levels.The use of salivary biomarkers has gained increased popularity since collecting samples is non-invasive and painless. The aim of thisstudy was to evaluate the level of cortisol in saliva among sample of university students having myofacial pain, during the final exam period and whether this finding could have a significant value as a symptomatic psychobiological marker. Materials and Methods: Ninety eight (98) university students were enrolled in this study. Fifty(50) were with myofacial pain (symptomatic) and forty eight (48) were without myofacial pain (asymptomatic) as a control group.Each student with myofacial pain was examined according to Research Diagnostic Criteria for Temporomandibular Disorders. Saliva sample were collected from each subject before final examination and three months later for biochemical analysis of cortisolusing ELISA test. Results: A highly significant difference in salivary cortisol level between the two periods for both the study and control groups, and a non-significant difference between the two groups in before examination period. A negative association has been observed between the level of salivary cortisol and severity of pain and a highly significant improvement of pain between the final examination periods and three months later. Conclusions: Dental students perceived a higher level of stress prior to the final exam was associated with raised salivary cortisol levels which could be considered as a useful non-invasive biomarker for measuring acute stress.